The Learning Outcomes of an Entrepreneurship Education Practice - Kantanen, Maisa (Finland, 2025)
Entrepreneurship education (EE) is an expanding field in higher education globally, employing diverse practices to produce various learning outcomes. These outcomes, intentional or not, are crucial for assessing the effectiveness of EE and guiding improvements in higher education. This paper explores the learning outcomes pursued in EE, focusing on cognitive, psychomotor, and affective domains as defined by the tripartite model of learning. Studies show that learning outcomes are interrelated and significantly influenced by the teaching approach, with practical, experience-based pedagogies yielding stronger entrepreneurial learning outcomes. Different types of EE courses lead to varied learning outcomes based on the students' initial entrepre-neurial intentions and motivation. This paper is based on an ethnographic case study of an in-tensive international EE program. It reveals the different learning outcomes of university stu-dents, contributing to the understanding of EE's impact. This research offers insights for plan-ning and evaluating EE practices in higher education.
Conference Proceedings : 22nd Nordic Conference on Small Business Research